Corrigendum to “Dissecting the Enterococcal Polysaccharide Antigen (EPA) structure to explore innate immune evasion and phage specificity” [Carbohydr. Polym. 347 (1 January 2025) 122686] - Jessica L. Davis; Joshua S. Norwood; Robert E. Smith; Finn O'Dea; Krishna Chellappa; Michelle L. Rowe; Mike P. Williamson; Graham P. Stafford; Evguenii Vinogradov; Emmanuel Maes; Yann Guérardel; Stéphane Mesnage (Carbohydrate Polymers, 2025)

Dissecting the Enterococcal Polysaccharide Antigen (EPA) structure to explore innate immune evasion and phage specificity - Jessica L. Davis; Joshua S. Norwood; Robert E. Smith; Finn O'Dea; Krishna Chellappa; Michelle L. Rowe; Mike P. Williamson; Graham P. Stafford; Evguenii Vinogradov; Emmanuel Maes; Yann Guérardel; Stéphane Mesnage (Carbohydrate Polymers, 2025)

Carbon stocks in marine habitats across Jersey’s territorial waters - Bede Ffinian Rowe Davies; Samantha Blampied; Francis Binney; Graham Epstein; Paul Chambers; Emma V. Sheehan (Regional Studies in Marine Science, 2024)

Integrating legacy soil phosphorus into sustainable nutrient management strategies for future food, bioenergy and water security - Helen Rowe; Paul J. A. Withers; Peter Baas; Neng Iong Chan; Donnacha Doody; Jeff Holiman; Brent Jacobs; Haigang Li; Graham K. MacDonald; Richard McDowell; Andrew N. Sharpley; Jianbo Shen; et al. (Nutrient Cycling in Agroecosystems, 2016)

Neglected native or undesirable alien? Resolution of a conservation dilemma concerning the pool frog Rana lessonae - Trevor J. C. Beebee; John Buckley; Ivor Evans; Jim P. Foster; Antony H. Gent; Chris P. Gleed-Owen; Geoffrey Kelly; Graham Rowe; Charles Snell; Julia T. Wycherley; Inga Zeisset (Biodiversity and Conservation, 2005)

Reconciling Genetic and Demographic Estimators of Effective Population Size in the Anuran Amphibian Bufo Calamita - Graham Rowe; T.J.C. Beebee (Conservation Genetics, 2004)

Isolation and characterization of microsatellite primers for the Fragrant Orchid Gymnadenia conopsea (L.) R. Brown (Orchidaceae) - Victoria V. Campbell; Graham Rowe; Trevor J.C. Beebee; Michael J. Hutchings (Conservation Genetics, 2002)

Application of Genetic Bottleneck Testing to the Investigation of Amphibian Declines: a Case Study with Natterjack Toads - Trevor Beebee; Graham Rowe (Conservation Biology, 2001)
Declines of amphibians are causing widespread concern and in some cases have been explained by factors such as climate change and the spread of microbial pathogens. A problem remains, however, in the unequivocal demonstration of decline in situations where populations may be undergoing natural fluctuations in abundance. We describe the application of a genetic test for bottlenecks () that should distinguish between natural oscillations and true population declines. British natterjack toads ( Bufo calamita ) provide examples of populations that have not declined in recent decades, populations that have declined, and populations in which trends are unclear. Microsatellite allele frequency data from these populations were tested for heterozygote excess and shifts in allele frequency distributions, and inferences from these computations about bottlenecks (i.e., persistently smaller population sizes than the recent means) were compared with demographic information. The genetic test correctly identified bottlenecks and should therefore prove useful in demonstrating whether amphibian declines have occurred where long‐term demographic time series are not available.

Application of Genetic Bottleneck Testing to the Investigation of Amphibian Declines: a Case Study with Natterjack Toads - Trevor Beebee; Graham Rowe (Conservation Biology, 2001)

A further four polymorphic microsatellite loci in the natterjack toad Bufo calamita - Graham Rowe; Trevor Beebee; Terry Burke (Conservation Genetics, 2000)

Polymerase chain reaction primers for microsatellite loci in the north European water frogs Rana ridibunda and R. lessonae - Inga Zeisset; Graham Rowe; Trevor J. C. Beebee (Molecular Ecology, 2000)

s of papers presented at the 63rd annual PAA meeting - Jose L. Rueda; Donald Berrios; W. R. Amoros; H. A. Mendoza; Jose Gil Archuleta; Gene D. Easton; C. R. Brown; Doug Bruce; Elsa Camadro; S. J. Peloquin; J. R. Davis; W. B. Jones; et al. (American Journal of Potato Research, 1979)